From Crisis to Recovery in Korea : Strategy, Achievements, and Lessons - Kang, Kenneth; Liang, Hong.; Ma, Henry; Richards, Anthony (Washington, D.C. : International Monetary Fund, 2001)
This paper reviews and draws lessons from the stabilization and reform program that Korea implemented in response to the 1997-98 crisis. The economy recovered quickly from the deep recession in 1998 and its vulnerability to a balance of payments crisis has been reduced sharply. Significant progress has also been made in stabilizing the financial system and addressing corporate distress, and wide-ranging reforms have made Korea's economy more open, competitive, and market driven. Notwithstanding these achievements, more needs to be done before the soundness of the corporate and financial sectors is firmly established.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet